MENINGKATKAN HASIL BELAJAR IPS POKOK BAHASAN PRANATA SOSIAL MELALUI PEMBELAJARAN BERBASIS MASALAH PADA SISWA KELAS VIII SMP NEGERI 2 KURIPAN KABUPATEN BARITO KUALA - Wahyu Wahyu (Universitas Lambung Mangkurat, 2015)
Learning social studies teacher at the school applied generally not maximized, is evident from the results of tests and observations during classroom learning social studies in grades completeness is still lacking and student activity is still low. This condition should be corrected by learning strategies so that learning can be meaningful for students in dealing with life problems that it faces in the future. Lessons are suitable for this is problem-based learning strategies. This study uses a Class Action Research (PTK) with a qualitative approach. Data collection techniques used were observation of teachers and students in learning activities. Learning outcomes measured by the initial test and final test on each cycle and analyzed using Anates program. The results showed that the activity of teachers through problem-based learning to obtain a score of 85.71 in the first cycle and 95.23 in the second cycle. Student learning activities also increased there the first cycle (meeting of 1 and 2) reached 78% and 79%, while the second cycle (meeting of 1 and 2) reached 81% and 88%. The study of students in the first cycle reaches 72.50 with classical completeness 80%, while the second cycle reaches 80.00 with classical completeness 95%. Through problem-based learning beneficial for students to foster creativity and improve learning achievement.Keywords: results of social studies, problem-based learning.